Analysis of genetic diversity among persimmon cultivars using microsatellite markers - Naval, María M.; Zuriaga, Elena; Pecchioli, Simona; Llácer, Gerardo; Giordani, Edgardo; Badenes, María L. (2017)
In the Mediterranean area, the production of persimmon (Diospyros kaki Thumb) [2n = 6x = 90] has increased recently as an alternative to the major fruit crops. In Spain, production relies almost exclusively on the cultivar “Rojo Brillante” which accounts for 83% of the crop. A crop based on a monovarietal culture implies several commercial risks that can compromise the future of the crop. Although the species was introduced in Europe very recently, it is well adapted to the climate of southern Europe. However, the recent introduction from Japan, the mistakes on the identity of varieties in the collections due to a bad translation of variety names from Japanese, and the lack of genetic characterization of many varieties have caused difficulties for effective management of the available genetic resources. The present paper was aimed at exploring the genetic diversity among different persimmon cultivars, including those collected in the European survey as well as Japanese cultivars. Seventy-one persimmon cultivars coming from two European collections that included accessions from Japan, Italy, and Spain were analyzed using 19 polymorphic microsatellite markers. A total of 206 alleles were obtained, with a mean value of 10.8 alleles per locus. A neighbor joining dendrogram and a principal coordinate analysis arranged the cultivars according to their genetic relationships. Analysis of molecular variance revealed significant genetic variability between and within groups, 73.3% and 85.2% for astringent-type and country origin, respectively. The simple sequence repeat markers classified the persimmon cultivars according to their genetic relationship.